2016
DOI: 10.1016/j.energy.2016.09.113
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a waste-heat driven adsorption system for automotive air-conditioning: Part I – Modeling and experimental validation

Abstract: Adsorption systems driven by engine waste heat are one of the possible alternatives to the conventional automobile air conditioning in terms of energy savings and environmental issues. Assessment of this issue are carried in a two-part study. In this first part I, theoretical and experimental investigations were performed on a two bed, silica gel adsorption chiller for automotive applications. A prototype adsorption system with a total weight of about 86 kg was developed and tested to driven by low-grade waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Nevertheless, advanced cycles such as heat recovery, mass recovery, thermal wave, and cascade cycle are all effective ways to improve the system performance of adsorption heat pump. Heat recovery process starts after the adsorption/desorption switch. Working fluid heated by the adsorber in the adsorption process flows to the other adsorber in the desorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, advanced cycles such as heat recovery, mass recovery, thermal wave, and cascade cycle are all effective ways to improve the system performance of adsorption heat pump. Heat recovery process starts after the adsorption/desorption switch. Working fluid heated by the adsorber in the adsorption process flows to the other adsorber in the desorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thermochemical energy materials allow for long-term energy storages as compared to PCMs, which are prone to thermal losses when stored for a long period. To date, metal hydrides, salts (e.g., metal halides) hydrates and ammoniates are the most utilized thermochemical materials for closed sorption systems driven by waste-heat intended for refrigeration [28][29][30][31][32][33][34], heat pumps and transformer applications [34][35][36][37]. The well-accepted layout of these sorption systems is two tanks interconnected, filled with a high temperature (HT) sorbent in one side, and a low temperature (LT) sorbent in the other side.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that cold and heat energy densities were 0.6 MJ·kg −1 and 1.498 MJ·kg −1 , respectively. Verde et al [29] investigated the performance of a prototype of waste-heat driven adsorption system for automotive air conditioning. The adsorption system was made of a two-tank silica gel adsorption chiller.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of heat exchangers are used in adsorbent beds such as plate-finned tubes, and a capillary tube bundle HE [12], a flatplate type HE with fins [13], a serpentine flat-pipe HE, and spiral plate HE [14]. Many researchers have proposed various types of sorption bed designs in order to enhance the heat transfer rate in the adsorbent bed [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1 (b). The system description, components, and the working principle of the system, silica gel-water air conditioning adsorption system, has been described in detail in our previous work [22,23]. The system was designed and tested under the framework of the TOPMACS project [30] for automotive air conditioning applications.…”
Section: Introductionmentioning
confidence: 99%